(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
This paper reviews the concept of Reproducibility Probability and makes a brief introduction to RP-testing. The RP-based version of some common parametric tests is provided. Moreover, a particular attention is devoted to the well-known nonparametric Wilcoxon Rank-Sum test. A comparison between the properties of the RP and the p-value is made in order to evaluate the practical utility of these stability indicators. It turns out that the use of the RP to perform the tests and to interpret their results, requires more technical analysis, but it provides more interpretable direct information on the stability of the test results.